Smoking Behavior Demarketing Model: Focus on Behavior, Not Intention - Widikusyanto, Muhammad Johan (Universitas Sultan Ageng Tirtayasa, 2023)
This research aims to develop a demarketing model that directly tests the influence of various factors on smoking behavior and formulate various strategies to reduce smoking behavior based on the model. The field of Marketing Science is typically employed to support or enhance the marketing of a product. The research on Demarketing Tobacco Use has evolved from using only one variable in the marketing mix to using all or four variables in the marketing mix. However, the existing Demarketing Tobacco Use or cigarette strategy still has limitations and needs to be further developed. The current Demarketing Tobacco Use strategy only tests the intention to quit smoking. This research is more accurate because it directly tests various factors that influence smoking behavior, not just testing the intention to smoke. The questionnaire was distributed to active smokers with a total of 595 respondents. The collected data was then analyzed using SEM. The findings of this study indicate that product, price, and promotion of cigarettes influence smoking behavior, while distribution does not. Based on these findings, several strategies can be formulated to reduce smoking behavior.Keywords: Demarketing; Marketing Mix; Smoking Behavior; Strategy